2008
DOI: 10.1007/s10745-007-9156-z
|View full text |Cite
|
Sign up to set email alerts
|

Herder Perceptions on Impacts of Range Enclosures, Crop Farming, Fire Ban and Bush Encroachment on the Rangelands of Borana, Southern Ethiopia

Abstract: This study focuses on community-based knowledge to analyze the impacts of range enclosures, crop farming, fire suppression and bush encroachment on the communal rangelands of Borana, southern Ethiopia. The knowledge of local herders is the basis for decision making in the utilization and management of grazing lands. We used Borana oral history associated with the period of the gada system to reconstruct environmental change that spans a period of 48 years. Our results show that the use of communities' percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
150
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(163 citation statements)
references
References 40 publications
11
150
2
Order By: Relevance
“…Furthermore, the pastoral communities indicated that the increase in encroacher woody plants in rangelands suppresses grass productivity, which reduces grazing area for livestock. This is in agreement with results of studies conducted in other parts of Botswana (Dougill et al 1999) and elsewhere (Angassa and Oba 2008b), which also show that bush encroachment is common in rangelands. Bush encroachment therefore threatens the livelihoods of pastoral communities (Angassa and Oba 2008a), especially in developing countries.…”
Section: Woody Vegetation Composition As Perceived By Pastoralistssupporting
confidence: 92%
“…Furthermore, the pastoral communities indicated that the increase in encroacher woody plants in rangelands suppresses grass productivity, which reduces grazing area for livestock. This is in agreement with results of studies conducted in other parts of Botswana (Dougill et al 1999) and elsewhere (Angassa and Oba 2008b), which also show that bush encroachment is common in rangelands. Bush encroachment therefore threatens the livelihoods of pastoral communities (Angassa and Oba 2008a), especially in developing countries.…”
Section: Woody Vegetation Composition As Perceived By Pastoralistssupporting
confidence: 92%
“…In African rangelands where scientific research is often patchy or non-existent, the pastoral communities have continued to rely on their systems of indigenous knowledge of rangeland management to make decisions that influence their livelihoods (Leach et al 1999;Kyagaba 2004;Mapinduzi et al 2003;Palmer and Wadley 2007;Angassa and Oba 2008;Roba and Oba 2009). In this study, we have used a research framework to understand how this knowledge functions using three case study communities.…”
Section: Discussionmentioning
confidence: 99%
“…The proper utilisation and management of grazing lands depends on the decision-making of the local herders (Angassa and Oba 2008). It is important, therefore, that the perceptions of herders match the knowledge that is available so that the appropriate decisions are made.…”
Section: Perception Of Herders To Climate Change the Rangeland Journalmentioning
confidence: 99%